Hippie woman wild a memoir of life & love on an Oregon commune - Schlanger, Carol (Wyatt-McKenzie Publishing, 2019)
A not-so-nice Jewish girl, expelled from Yale Drama during the Vietnam protests, abandons her acting dream to follow the man she loves to an off-the grid commune in Oregon